The Association Between Student Reports of Classmates' Disruptive Behavior and Student Achievement. (June 2016) - Blank, Carmel; Shavit, Yossi
Classroom disciplinary climate and its correlation to students' performance is a widely debated issue. Policy reports tend to assume that classroom disruptions interfere with the learning experience. Empirical evidence for this assumption, however, which carefully distinguishes classroom climate from the school climate in general, is still wanting. This study examines the relation between student reports regarding disciplinary infractions to student achievement, with a special focus on classroom disruptions. Multilevel regressions were used to estimate the contribution of classroom and school disciplinary infractions on eighth-grade students' test scores. Reports of disruptive behavior proved to correlate negatively with test scores, whereas the effect of other school and classroom characteristics, including teachers' attitudes and school disciplinary policy, were insignificant (controlling for students' prior achievements). We conclude that a disruptive classroom climate can hinder the learning process and lower the achievement of the entire class, regardless of the conduct of any particular student. Therefore, a special focus on disruptions in the classroom, in contradistinction with school disciplinary climate in general—which is lacking in most studies—emerges as instrumental to the understanding of how school climate relates to student achievement.